2021
DOI: 10.1016/j.onehlt.2021.100292
|View full text |Cite
|
Sign up to set email alerts
|

A three-phase population based sero-epidemiological study: Assessing the trend in prevalence of SARS-CoV-2 during COVID-19 pandemic in Jordan

Abstract: The evolution of the COVID-19 pandemic in Jordan during the first 10 months of the epidemic was peculiar and can be easily categorized in three different phases: a first period featuring a very low number of reported cases, a second period with exponential growth from August with up to 8000 cases on the 18th November 2020, and a third phase with steady and progressive decline of the epidemiological curve. With the aim of better determine the entity of the population exposed to SARS-CoV-2, the Jordan Ministry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…The low estimated seroprevalence among residents of Oman in the first two cycles is comparable to other population-based studies that have been conducted around the same period or before it (Bellizzi et al, 2021;Pollán et al, 2020;Alsuwaidi et al, 2021) Over the 19 study weeks, we observed an increase in seroprevalence from about 5% to about 22% which is to be expected considering time to seroconversion after symptoms and that the peak of the first wave of the epidemic was reached the week before the start of the first cycle, and the fourth cycle was conducted after the end of the second peak (see Figures 1 and 2). The increase in seroprevalence was similar to findings from other studies (Stringhini et al, 2020;Bellizzi et al, 2021;Murhekar et al, 2021;Hallal et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The low estimated seroprevalence among residents of Oman in the first two cycles is comparable to other population-based studies that have been conducted around the same period or before it (Bellizzi et al, 2021;Pollán et al, 2020;Alsuwaidi et al, 2021) Over the 19 study weeks, we observed an increase in seroprevalence from about 5% to about 22% which is to be expected considering time to seroconversion after symptoms and that the peak of the first wave of the epidemic was reached the week before the start of the first cycle, and the fourth cycle was conducted after the end of the second peak (see Figures 1 and 2). The increase in seroprevalence was similar to findings from other studies (Stringhini et al, 2020;Bellizzi et al, 2021;Murhekar et al, 2021;Hallal et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…There was also earlier spread in the governorates on the borders of other countries. Regional variations in SARS-CoV-2 seroprevalence have also been reported in many other countries (Bellizzi et al, 2021;Pollán et al, 2020;Alsuwaidi et al, 2021;Poustchi et al, 2021;Núñez-Zapata et al, 2021).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This is result is consistent with other studies which found a statistical significance between IgG positivity and gender, [14], [15]. At the regional level, a three phased seroprevalence survey was conducted in Jordan, where results revealed that seroprevalence dramatically increased over time, with only a tiny fraction of seropositive individuals in August (0.3%), to increase up to more than 20-fold in October (7.0%) and to reach one-third of the overall population exposed by the end of 2020 (34.2%), [15]. Such results are compatible with similar seroprevalence survey conducted by the Palestinian ministry of health and WHO at the end of 2020.…”
Section: Discussionsupporting
confidence: 94%
“…Since the emergence of SARS-CoV-2, assessing and understanding the kinetics and protective role of the human immune response against this virus, has been of a high priority and relevance [ 4 ]. For this purpose, different investigations have conducted several seroepidemiological surveys worldwide to measure the seroprevalence of antibodies against SARS-CoV-2 [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. These studies have demonstrated the importance of the humoral immune response for the elimination of viral infection, and the important role of understanding the dynamics of antibodies against SARS-CoV-2, which help not only in assessing immunological levels and predicting potential immune protection, but also in the development of vaccine and immune therapy strategies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%